Pemberdayaan Suku Hubula di Kampung Sereh Sebagai Komunitas Urban - Wantik, Marnius; Lefaan, Avelinus; Mansoben, J. R. (Universitas Cenderawasih, 2023)
This article aims to examine the empowerment of the Hubula tribal community in Kampung Sereh as an urban community in improving the family economy. By looking at the motivation for urbanization, then the empowerment process and the obstacles faced. This research is descriptive field research, which is a fact search that can reveal an object being researched without any engineering. The author took data through samples using a sampling proposal. Based on the criteria that the author provides, the sample is 10 people. The tools used by the author to collect data are the results of documentation, observation and interviews. Data analysis includes a series of data reduction, data presentation and drawing conclusions. The results of this research show that the motivation for urbanization of the Hbula community is motivated by 5 factors, namely, contact with the outside world, continuing education, because of illness, practical politics, and seeking treatment. The empowerment process by becoming farmers, traders and breeders as well as the motivation to improve the family economy. The obstacles encountered are limited access to land cultivation, the existence of a residence, business capital management, too much focus as a missionary employee and a culture of laziness that is still strongly embedded.